Serum Secretagogin and Focal Adhesion Kinase as Markers for Type 2 Diabetes Mellitus and Beta Cells Function - Shahad Ali Al-Eqabi1, Zeena Abdul llah1, Mahmood Shakir Khudhair2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Diabetes mellitus (DM) is one of the world’s major public health problems. The increasing incidence of DM worldwide makes it a leading cause of morbidity and mortality for the anticipated future. Secretagogin (SCGN) is a protein enriched and secreted from pancreatic islets, it demonstrates protective effects on ?-cell function. Focal adhesion kinase (FAK) plays a critical role in ?-cell survival and is a vital regulator of insulin secretion. In this research, serum SCGN, FAK, fasting blood glucose (FBG), HbA1c, C-peptide, lipid profile, blood urea nitrogen (BUN) and creatinine were measured in patients diagnosed with type 2 diabetes mellitus (T2DM) and in healthy volunteers. The results showed that there was a significant increase in the levels of serum SCGN in patients with T2DM compared to the control group. There was a significant decrease in levels of FAK and C-peptide in T2DM patients compared to the control group. In addition, a significant increase was seen in FBG and HbA1c levels in T2DM patients compared to the control group. The lipid profile of T2DM patients was altered compared to the control group. There was no significant difference in the levels of BUN and creatinine among the study subjects. The results of this study suggest that both SCGN and FAK may serve as potential biomarkers reflecting the state of islet cells dysfunction in T2DM patients which may present additional markers for the diagnosis of T2DM.